58 Strategies to optimise guideline-directed medical therapy in heart failure patients with reduced ejection fraction by improving SGLT2i initiation rates in nurse-led outpatient heart failure clinics. (6th October 2022) - Soh, BWT; Cusack, R; O'Brien, K; Glasgow, J; Forkin, A; Abbas, S; Arnous, S; Kiernan, T
Abstract : Background: Heart failure with reduced ejection fraction (HFrEF) is a complex disease, with multiple comorbidities, making management with guideline-directed medical therapy (GDMT) a challenging feat. Nurse-led outpatient HF clinics play a pivotal role in the optimisation of GDMT in HFrEF patients, with established benefits in reducing hospitalization and mortality. The recent addition of sodium-glucose transport protein 2 inhibitors (SGLT2i) to the backbone of HFrEF disease-modifying therapy has further increased the complexities of HF management. Prescriber hesitancy of SGLT2i in nurse-prescribers is compounded by concerns of treatment side effects, comorbidities, polypharmacy, and patient hesitancy. The lack of SGLT2i initiation in nurse-led clinics is under-investigated and may result in lower rates of patients receiving appropriate GDMT. Considering the widespread use of nurse-led outpatient HF clinics in Ireland, this trend could have widespread implications depending on the rate of SGLT2i initiation by nurse-prescribers. Purpose: To describe the rate of SGLT2i use in a nurse-led outpatient HF clinic (HFSU) and the impact of developing local nurse-prescriber guidelines on improving SGLT2i initiation rates. Methods: A retrospective closed-loop clinical audit was performed on HFrEF patients actively attending the HFSU. HFrEF was defined as left ventricular ejection fraction (LVEF) ≤40% and active attendance was defined as a single HFSU engagement within one year, and patients who have not died, been transferred to another service, or lost to follow-up. Patients who attended the HFSU during the respective phases had information on patient demographic, comorbidities, baseline investigations, and pharmacotherapy patterns collected and compared: Pre-intervention (January 2021 to December 2021), and Post-intervention (January 2022 to April 2022). Nurse-prescriber guidelines and patient information leaflets were developed and initiated as an intervention in January 2022. Results: A total of 320 HFrEF patients were actively attending the HFSU during the Pre- and Post-intervention phases (160 Pre-intervention vs 160 Post-intervention) ( table 1 ). During the Pre-intervention phase, SGLT2i was used in 9 patients (5.6%) who were all comorbid with type 2 diabetes mellites (T2DM). After intervention, SGLT2i use was significantly higher in the Post-intervention group when compared to the Pre-intervention group (9 (5.6%) vs 34 (21.3%), P <0.0001) ( table 1 ). 16 of the 34 patients on SGLT2i in the Post-intervention group were comorbid with T2DM. Conclusions: Prescriber hesitancy of SGLT2i is an ongoing issue in nurse-led outpatient HF clinics. Auditing pharmacotherapy patterns can identify current rates of SGLT2i initiation, alerting clinicians to inadequate GDMT rates. Local nurse-prescriber guidelines and patient information leaflets can effectively increase the rate of SGLT2i initiation by non-physician prescribers and extend its licensed use beyond the diabetic cohort.